(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Nutrition education within pharmacy curricula plays a pivotal role in equipping future pharmacists with the knowledge and skills necessary to address the complex interplay between diet and health outcomes. This abstract explores the current landscape of nutrition education in pharmacy programs, highlighting the variability in coursework and the need for enhanced integration. Key components of nutrition education, including essential topics and innovative teaching methods, are discussed, alongside successful models and best practices from pharmacy schools. The role of accreditation standards and professional organizations in promoting nutrition education is also examined. This abstract underscores the importance of prioritizing nutrition education in pharmacy curricula to better prepare pharmacists for their integral role in promoting optimal health and wellness.